(untitled) (Research, Society and Development, 2022)
What role does Toyism play in the flexible labor and capital relationship? The Toyotist production model not only influenced the production of cars, but in several categories, such as education. The capitalist system determines education, as it is directly linked to knowledge for the production of material. With the advancement of Toyotism, in addition to flexible production, flexible education emerged, driven by integral, technical schools, directly linked to Professional, Technological Education (EPT). The article aims to make a relationship between Toyotism, flexible work and capital, and its interference in labor relations and professional education, as well as to weave about the perspectives of professional education in the face of globalized capital. The study is of a qualitative nature, being a bibliographical research in books, articles, magazines and so on. It is based on historical and dialectical materialism and will count on the contribution of theorists such as: Moura (2007), Kuerzen (2016), Grabowosk (2016) among others. It was possible to understand the relationship between Toyotism and globalized capital, as well as the existing work relationships. It is evident that social transformations and evolutions stimulate labor changes and evolutions, and these evolutions are determinant to the educational process, which produces knowledge for materiality.